Antinociceptive Effect of Silymarin in Experimental Animals - Sahib, *Ahmed S. (AL-Kindy College Medical Journal, 2011)
Background: Silymarin is a polyphenolic flavonoid derived from milk thistle (Silybum marianum) that has anti-inflammatory, cytoprotective, anticarcinogenic and antioxidant effects. It has been used medicinally to treat liver disorders including acute and chronic viral hepatitis, toxin/drug induced hepatitis, and alcoholic liver disease. Objective: To evaluate the antinociceptive effect of silymarin in experimental animal model of pain. Methods: The efficacy and dose response effect of silymarin (125, 250, and 500mg/kg) were assessed against control using tail flick test in mice as a model of nociceptive pain. In this model, all doses of silymarin were given intraperitoneally 15 min before immersion of tail in hot water 50°C, and Tail Flick Latency was measured before, and after (15, 30, 60 and 120 min) administration of silymarin. Result: Silymarin in 250 and 500mg/kg significantly increase Tail Flick Latency after 15, 30, 60 and 120 min in a dose dependent manner that the maximum effect seen after 120 min compared to baseline value. Conclusion: Silymarin as a herbal drug produce a significant antinociceptive effect in experimental animal model of pain, and beside its better standardization, quality control, and safety profile, in addition to its availability and relative low cost, represent a good alternative choice for management of pain.